Implementation of Visual, Auditory, and Kinesthetic (VAK) Differentiated Learning to Improve Scientific Communication Skill in Science Subjects - Fitra, Devi Kurnia; Copriady, Jimmi; Zulirfan, Zulirfan (Journal of Natural Science and Integration, 2025)
This study aims to improve students' scientific communication skills through the implementation of differentiated VAK (Visual, Auditory, and Kinesthetic) learning in the "Motion and Force" topic for Grade VII of junior high school, in response to the demands of the Independent Curriculum, which emphasizes student-centered learning by accommodating diverse learning needs. This quantitative research employed a quasi-experimental approach with a Nonequivalent Pretest-Posttest Control Group Design. The study involved 100 students from SMPN 1 Tembilahan, divided into experimental and control groups. Data analysis was conducted both descriptively and inferentially to assess the impact of VAK-differentiated learning compared to conventional scientific learning methods on the enhancement of scientific communication skills. Scientific communication abilities were evaluated based on six indicators: information retrieval, scientific reading, scientific writing, listening and observation, information representation, and knowledge presentation. Pretests and posttests were administered to both groups. The results showed that the average posttest scores of the experimental group were significantly higher than those of the control group. Furthermore, the MANOVA test confirmed a significant difference in the improvement of scientific communication skills between the groups, indicating that VAK-differentiated learning effectively supports the development of scientific communication competencies among students.Keywords: scientific communication, VAK differentiation